Efeitos patrimoniais do mandado de segurança: interpretação constitucional das Súmulas 269 e 271 do Supremo Tribunal Federal - Dorna, Mário Henrique de Barros (2019)
This work recovers the writ of mandamus history in Brazilian Law to comprehend it, in the light of the constitutional model, with the purpose to interpret, adequately and strictly, precedents n. 269 and 271 of the Federal Supreme Court. Stem from strong hermeneutic and methodological premises, the affirmations made by part of the doctrine and many judgments in the sense that the writ of mandamus can substitute actions for debt and about the possibility of producing past patrimonial effects are wrong. The systematic interpretation of Law, conjugating constitutional and legal rules, procedural and material law, such as the analysis of a collection of judgments, leads to the systematization of rules that reveal flaws of both precedents (269 and 271 of the Federal Supreme Court), whose assertions do not fulfil the mission to extern, with clarity and precision, the interpretation of the legal rule. In conclusion, during history, certain restrictions were assigned to the writ of mandamus and to the procedure law rules, generically, concerning material law that rules determined situations subject to writ of mandamus. Comprehending the origin of the imposed restrictions by precedents 269 and 271 of the Federal Supreme Court such as the situations in which they legitimately apply is fundamental to preserve (read: to recover) acting field of this essential and formidable constitutional guarantee that is the writ of mandamus